Enhancing faculty members’ skills in using digital libraries through interactive virtual reality training: A case study at Omar Al-Mukhtar University - Dr. Amal Mohamed Fahdel; Salmeen Mohammed Hamza (Journal of Scientific and Human Dimensions, 2025)
This study aims to answer the main question: What is the impact of using interactive virtual reality training on developing faculty members’ skills in using digital libraries at Omar Al-Mukhtar University? This study highlights the importance of enhancing faculty members’ skills and empowering them to effectively utilize digital resources, thereby positively impacting the quality of education and scientific research. It also emphasizes the benefits of information services in digital libraries within universities, particularly at Omar Al-Mukhtar University, the subject of this research. The study aims to explore the use of interactive virtual reality training as an innovative training method to develop faculty members’ digital and informational skills in their academic and research activities, enabling them to access electronic resources effectively. Furthermore, the study contributes scientific findings that can be used to design future training programs based on modern interactive technology. This research seeks to address a clear knowledge gap: the lack of research employing interactive virtual reality training to develop digital skills in higher education institutions and keep pace with the developments and changes occurring in the knowledge-based world. The study focuses on a key academic group that contributes to disseminating research culture. A descriptive-analytical approach was used, relying on a questionnaire as the primary tool for data collection and analysis to arrive at accurate conclusions about the participants’ performance. The study presents a practical, measurable, and applicable training model within a real academic environment. The study’s strength lies in its novel subject matter, its integration of technology and academic professional development, and its contribution to supporting digital transformation in Libyan universities.